2010
DOI: 10.1590/s1807-59322010001200003
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and ultrastructural analysis of surgical lung biopsies in patients with swine-origin influenza type A/H1N1 and acute respiratory failure

Abstract: BACKGROUND:Cases of H1N1 and other pulmonary infections evolve to acute respiratory failure and death when co‐infections or lung injury predominate over the immune response, thus requiring early diagnosis to improve treatment.OBJECTIVE:To perform a detailed histopathological analysis of the open lung biopsy specimens from five patients with ARDS with confirmed H1N1.METHODS:Lung specimens underwent microbiologic analysis, and examination by optical and electron microscopy. Immunophenotyping was used to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
(39 reference statements)
1
34
0
2
Order By: Relevance
“…They were randomly assigned to left coronary artery occlusion or sham surgery and found that previous swim training does not attenuate systolic and diastolic function alterations after myocardial infarction induced by left coronary artery occlusion, suggesting that cardioprotection cannot be provided by exercise training in this experimental model. Capelozzi et al [54] performed a histopathological analysis of the open lung biopsy specimens from five patients with ARDS with confirmed H1N1 and claim that viral-like particles can be successfully demonstrated in lung tissue by ultrastructural examination, without confirmation of the virus by RT-PCR on nasopharyngeal aspirates. Bronchioles and epithelium, rather than endothelium, are probably the primary target of infection, and diffuse alveolar damage the consequence of the effect of airways obliteration and dysfunction on innate immunity, suggesting that treatment should be focused on epithelial repair.…”
Section: Kk and Rocha E Silva M -Cardiology In Brazilian Scientific Joumentioning
confidence: 99%
“…They were randomly assigned to left coronary artery occlusion or sham surgery and found that previous swim training does not attenuate systolic and diastolic function alterations after myocardial infarction induced by left coronary artery occlusion, suggesting that cardioprotection cannot be provided by exercise training in this experimental model. Capelozzi et al [54] performed a histopathological analysis of the open lung biopsy specimens from five patients with ARDS with confirmed H1N1 and claim that viral-like particles can be successfully demonstrated in lung tissue by ultrastructural examination, without confirmation of the virus by RT-PCR on nasopharyngeal aspirates. Bronchioles and epithelium, rather than endothelium, are probably the primary target of infection, and diffuse alveolar damage the consequence of the effect of airways obliteration and dysfunction on innate immunity, suggesting that treatment should be focused on epithelial repair.…”
Section: Kk and Rocha E Silva M -Cardiology In Brazilian Scientific Joumentioning
confidence: 99%
“…Primary pandemic influenza A H1N1 pneumonia has been emerged in 2009 with a high mortality rate. Autopsy reports of the patients with H1N1 pneumonia showed severe hemorrhagic pneumonitis, interstitial inflammation and diffuse alveolar damages (Capelozzi et al, 2010). In this local outbreak viral pneumonia, the major cause of mortality was ARDS and we found the mortality rate of influenza A (H1N1) as 4.23% in outpatient department, 23.8% in hospitalized cases with pneumonia and 100% in cases complicated with peumonia and ARDS and admitted to ICU.…”
Section: Discussionmentioning
confidence: 71%
“…Capelozzi et al (27) report a detailed histopathological analysis of open lung biopsy specimens from five patients with acute respiratory distress syndrome and confirmed H1N1 infection, which was evidenced by viral-like particles in lung tissue, as identified through ultrastructural examination. Bronchioles and epithelium, rather than endothelium, seem to be the primary targets of H1N1 infection.…”
Section: Infectious Diseasesmentioning
confidence: 99%